Comparative analysis of surgical outcomes: Video-assisted thoracoscopic surgery versus open thoracotomy in organizing thoracic empyema management - Thanat Suwanarawat; Rachata Deesang; Sasikarn Tawanseree; Sikkawat Watcharasoonthonkit; Somcharoen Saeteng; Sophon Siwachat; Apichat Tantraworasin (PLoS ONE, 2025)
Background Surgical intervention is essential for managing organizing thoracic empyema, but the efficacy of Video-Assisted Thoracic Surgery (VATS) in this disease stage remains debated. This study aims to compare the surgical outcomes of VATS versus open thoracotomy (OT) in the management of organizing thoracic empyema. Materials and methods This retrospective cohort study included 393 patients who underwent surgery for organizing thoracic empyema at Maharaj Nakorn Chiang Mai Hospital between January 1, 2012, and December 31, 2022, and were divided into VATS and OT groups. The primary outcomes were lung full expansion before discharge and at the 2-week follow-up. Secondary outcomes included intraoperative blood loss, duration of intensive care unit (ICU) stay, and postoperative pain scores. Data analysis was performed using multivariable regression analysis and propensity score matching. Results In the propensity-matched cohort (212 patients), patient characteristics were balanced between the two groups. VATS was associated with a higher likelihood of full lung expansion at discharge (risk ratio: 1.21; 95% CI: 1.01 to 1.45compared to OT. There were no significant differences in postoperative pain scores, or full lung expansion at 2 weeks after discharge between the two groups. However, the VATS group showed a trend toward less intraoperative blood loss (mean difference: −34.20; 95%CI: −162.89 to 94.49). Conclusions VATS offers advantages over OT in organizing thoracic empyema surgery, particularly in terms of improved lung expansion at discharge. Further studies with larger sample sizes are warranted to support these findings.